At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the solutions to the quadratic equation [tex]\( x^2 - 10x = -34 \)[/tex], we'll follow these steps:
1. Rewrite the equation in standard quadratic form.
First, bring all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 10x + 34 = 0 \][/tex]
2. Identify coefficients for the quadratic formula.
The standard quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. In this equation:
[tex]\[ a = 1, \quad b = -10, \quad c = 34 \][/tex]
3. Use the quadratic formula.
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substitute in the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4 \cdot 1 \cdot 34}}{2 \cdot 1} \][/tex]
4. Simplify the equation.
Calculate inside the square root:
[tex]\[ x = \frac{10 \pm \sqrt{100 - 136}}{2} \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{-36}}{2} \][/tex]
Simplify the expression under the square root:
[tex]\[ x = \frac{10 \pm \sqrt{36} \cdot i}{2} \][/tex]
[tex]\[ x = \frac{10 \pm 6i}{2} \][/tex]
5. Split the equation into two solutions.
[tex]\[ x = \frac{10 + 6i}{2} \quad \text{and} \quad x = \frac{10 - 6i}{2} \][/tex]
Simplify each fraction:
[tex]\[ x = 5 + 3i \quad \text{and} \quad x = 5 - 3i \][/tex]
So, the solutions to the equation [tex]\( x^2 - 10x = -34 \)[/tex] are:
[tex]\[ x = 5 \pm 3i \][/tex]
Therefore, the correct answer is B. [tex]\( x = 5 \pm 3i \)[/tex].
1. Rewrite the equation in standard quadratic form.
First, bring all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 10x + 34 = 0 \][/tex]
2. Identify coefficients for the quadratic formula.
The standard quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. In this equation:
[tex]\[ a = 1, \quad b = -10, \quad c = 34 \][/tex]
3. Use the quadratic formula.
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Substitute in the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4 \cdot 1 \cdot 34}}{2 \cdot 1} \][/tex]
4. Simplify the equation.
Calculate inside the square root:
[tex]\[ x = \frac{10 \pm \sqrt{100 - 136}}{2} \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{-36}}{2} \][/tex]
Simplify the expression under the square root:
[tex]\[ x = \frac{10 \pm \sqrt{36} \cdot i}{2} \][/tex]
[tex]\[ x = \frac{10 \pm 6i}{2} \][/tex]
5. Split the equation into two solutions.
[tex]\[ x = \frac{10 + 6i}{2} \quad \text{and} \quad x = \frac{10 - 6i}{2} \][/tex]
Simplify each fraction:
[tex]\[ x = 5 + 3i \quad \text{and} \quad x = 5 - 3i \][/tex]
So, the solutions to the equation [tex]\( x^2 - 10x = -34 \)[/tex] are:
[tex]\[ x = 5 \pm 3i \][/tex]
Therefore, the correct answer is B. [tex]\( x = 5 \pm 3i \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.